2019
DOI: 10.1021/acsami.9b18043
|View full text |Cite
|
Sign up to set email alerts
|

Alkanethiol Molecular Barriers for Controlling Small Molecule Release Kinetics from a Microgel-Based Reservoir Device

Abstract: Poly­(N-isopropylacrylamide)-co-acrylic acid microgel-based reservoir devices were constructed by “sandwiching” a single layer of microgels between two thin Au layers (all on a glass support). The microgels were loaded with the model drug crystal violet (CV) utilizing the electrostatic interactions between deprotonated acrylic acid (AAc) and the positively charged CV; release can be triggered from the microgels by neutralizing the deprotonated AAc groups at acidic conditions. Alkanethiols of different alkyl ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Guo et al followed this study by adding a self-assembled alkane-thiol coating on the gold overlayer to reduce the CV diffusion rate and enable accurate monitoring of the CV transport. [230] The team found that short alkane chains (C-2 to C-6) displaying hydrophilic terminal groups increased the diffusion rate up to 5-fold compared to unmodified etalons. At the same time, long-chain hydrocarbons (C-11 to C-15) slowed CV diffusion from the sensor by nearly 10-fold.…”
Section: Controlled Releasementioning
confidence: 99%
“…Guo et al followed this study by adding a self-assembled alkane-thiol coating on the gold overlayer to reduce the CV diffusion rate and enable accurate monitoring of the CV transport. [230] The team found that short alkane chains (C-2 to C-6) displaying hydrophilic terminal groups increased the diffusion rate up to 5-fold compared to unmodified etalons. At the same time, long-chain hydrocarbons (C-11 to C-15) slowed CV diffusion from the sensor by nearly 10-fold.…”
Section: Controlled Releasementioning
confidence: 99%
“…At pH < 4.25, the PAAc chains are protonated and become neutralized. 44,45 The anionic charge property of the microgels also enables their interaction with cationic proteins. 46 For example, high protein drug (cytochrome c) loading capacity (more than 9.7 × 10 5 protein molecules/ microgel particle) has been achieved in a previous study due to the formation of the polymer (PNIPAAm-co-AAc)−protein complexes and the porous structure of the microgels.…”
Section: ■ Introductionmentioning
confidence: 99%